Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4236/iim.2017.92003
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Survey on Arabic Stemming: Approaches and Challenges

Abstract: Arabic, as one of the Semitic languages, has a very rich and complex morphology, which is radically different from the European and the East Asian languages. The derivational system of Arabic, is therefore, based on roots, which are often inflected to compose words, using a spectacular and a relatively large set of Arabic morphemes affixes, e.g., antefixs, prefixes, suffixes, etc. Stemming is the process of rendering all the inflected forms of word into a common canonical form. Stemming is one of the early and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The same results were obtained by Al-Badarneh et al [27] and Mustafa et al [43], which demonstrated that stem is a better choice to use in classifying Arabic text. Our obtained result is consistent with the finding of Liu and Zhang [45] which showed that the pre-processing steps like stemming improves SA accuracy.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The same results were obtained by Al-Badarneh et al [27] and Mustafa et al [43], which demonstrated that stem is a better choice to use in classifying Arabic text. Our obtained result is consistent with the finding of Liu and Zhang [45] which showed that the pre-processing steps like stemming improves SA accuracy.…”
Section: Resultssupporting
confidence: 83%
“…Stemming [43] is among the most important pre-processing steps in mining opinions as well as a very common requirement for natural language processing (NLP). Stemming standardises words by reducing each word to stem, base or root form.…”
Section: Our Approachmentioning
confidence: 99%
“…The used datasets in these reported studies are very varied also and the majority of the employed test collections are not standard. In [3] the authors of this paper provide a complete survey for the developed algorithms of Arabic IR.…”
Section: Related Workmentioning
confidence: 99%
“…In contemporary time, the term Arabic has three forms [3] [4]: Classical Arabic (CA), Modern Standard Arabic (MSA) and Dialectal Arabic. Classical Arabic was the language of old Arabic-speaking people, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation